Pseudomonas aeruginosa isolates from dental unit waterlines can be divided in two distinct groups, including one displaying phenotypes similar to isolates from cystic fibrosis patients - Ouellet, Myriam M.; Leduc, Annie; Nadeau, Christine; Barbeau, Jean; Charette, Steve J. (Frontiers in Microbiology, 2015)
Pseudomonas aeruginosa displays broad genetic diversity, giving it an astonishing capacity to adapt to a variety of environments and to infect a wide range of hosts. While many P. aeruginosa isolates of various origins have been analyzed, isolates from cystic fibrosis patients have received the most attention. Less is known about the genetic and phenotypic diversity of P. aeruginosa isolates that colonize other environments where flourishing biofilms can be found. In the present study, 29 P. aeruginosa isolates from dental unit waterlines and cystic fibrosis patients were collected and their genetic and phenotypes profiles were compared to determine whether environmental and clinical isolates are related. The isolates were first classified using the random amplified polymorphic DNA (RAPD) method. This made it possible to distribute the isolates into one clinical cluster and two environmental clusters. The isolates in the environmental cluster that were genetically closer to the clinical cluster also displayed phenotypes similar to the clinical isolates. The isolates from the second environmental cluster displayed opposite phenotypes, particularly an increased capacity to form biofilms. The isolates in this cluster were also the only ones harboring genes that encoded specific epimerases involved in the synthesis of lipopolysaccharides, which could explain their increased ability to form biofilms. In conclusion, the isolates from the dental unit waterlines could be distributed into two clusters, with some of the environmental isolates resembled the clinical isolates.